Cyber-Cosmos: A new citizen science concept in a dark sky destination. (November 2022) - Barbosa, Domingos; Coelho, Bruno; Bergano, Miguel; Magalhães, Catarina; Mendonça, David; Silva, Daniela; Correia, Alexandre C.M.; Pandeirada, João; Ribeiro, Valério; Esposito, Thomas; Marchis, Franck
Abstract: Astrotourism and related citizen science activities are becoming a major trend of a sustainable, high-quality tourism segment, core elements to the protection of Dark skies in many countries. In the Summer of 2020, in the middle of COVID pandemics, we started an initiative to train young students – Cyber-Cosmos – using an Unistellar eVscope, a smart, compact and user-friendly digital telescope that offers unprecedented opportunities for deep-sky observation and citizen science campaigns. Sponsored by the Ciência Viva Summer program, this was probably the first continuous application of this equipment in a pedagogical and citizen-science context, and in a pandemic context. Pampilhosa da Serra, home to a certified Dark Sky destination (Aldeias do Xisto) in central Portugal, was the chosen location for this project, where we expect astrotourism and citizen science to flourish and contribute to space sciences education. Highlights: Astrotourism and citizen science are core elements to the protection of Dark skies. Smart telescopes to support science missions (Lucy, TESS, Plato, ARIEL, James Webb). First demo activity in a COVID-19 pandemic context Supported by Pampilhosa da Serra Space Observatory for SSA activities. Presentation at the 72nd IAC, Dubai, United Arab Emirates, 25–29 October 2021, as paper 66604, session on space culture.